Dosimetria pré-clínica no desenvolvimento de novos radiofármacos através de simulação por código de Monte Carlo - Silva, Catherine Costa Oliveira da (2017)
For the research and development of new radiopharmaceuticals in Nuclear Medicine, it is essential to estimate internal absorbed dose distribuition in the preclinical phase. However, the internal dosimetry is not a trivial procedure, and the development of more accurate methodologies has been the subject of intense research. The purpose of this study was the developement of a dosimetric tool by Monte Carlo simulation to be applied in preclinical research in the development of new radiopharmaceuticals. A voxelized phantom was developed from Computed Tomography (CT) images of a mouse type C57BL/6 to be connected to the GATE Monte Carlo code, version 7.1, with the aim to calculate the S-values for each organ source and to estimate absorved doses in target organs for 18F-FDG and 99mTc-Ixolaris radiopharmaceuticals. In general, the mass values of the simulator developed in this study agreed with the proposed model by XIE and ZAIDI (2013). The organs that received the highest doses of radiation were the source organs and those located near them. The simulation procedure was validated comparing S-values obtained for 18F source with the values reported in the literature, with results very close to the literature, with discrepances ranging from 2 to 47 %, since the organ masses were different. The methodoly developed in this study will be inserted in the Deparment of Nuclear Medicine research from HU/UFRJ in order to assist preclinical studies of biodistribution and dosimetry, fundaental to the development of new radiopharmaceuticals.